Hubungan Status Gizi dengan Kejadian Hipertensi pada Wanita Usia Subur (WUS) di Kelurahan Sadeng Gunung Pati Kota Semarang - Christina Ary Yuniarti; Mirza Fathan Fuadi; Zidna Sabela Naja (Lembaga Pengembangan Kinerja Dosen, 2024)
Non-communicable diseases (NCDs) are one of the biggest health challenges globally. Based on data from the World Health Organization or WHO, data shows that of the 56 million deaths that occurred in the world in 2021, there were 38 million or almost three quarters. Based on data from the Semarang City Health Service, the gender of those receiving health services for Hypertension Sufferers in 2022 shows that the female gender is 161,877 (56%) which is greater than the male gender which is 129,033 (44%), and in the working area of ​​the Gunungpati Community Health Center it is in the fifth highest position. Hypertension sufferers. Nutritional status is also influenced by a good diet and is also influenced by age, especially in women of childbearing age less than 40 years because they have a greater potential for experiencing hormonal imbalances in the body. The respondents in this research were WUS in the Sadeng Gunung Pati sub-district, Semarang city, totaling 101 respondents. The aim of this study was to determine the relationship between nutritional status and the incidence of hypertension in suburban age women (WUS) in the Sadeng Gunung Pati sub-district, Semarang City. This research method uses a cross sectional approach which was carried out in the Sadeng Gunung Pati sub-district. Data collection was carried out from March to May 2024. The results showed that the correlation between nutritional status and the incidence of hypertension in women of childbearing age (WUS) in Sadeng subdistrict was carried out using the Chi Square test, obtained with a P value = 0.0001, OR = 5.15 , CI = (2.16 – 12.26), where the majority of respondents with hypertension were 57.4% (aged 15-49 years) with a BMI classification in the thin category of 18.5. The conclusion of this study is that there is a relationship between nutritional status and the incidence of women of suburban age (WUS) in the Gunung Pati sub-district, Semarang city.